The environment, sustainable development, and public policies : building sustainability in Brazil - Cavalcanti, Clóvis de Vasconcelos (Cheltenham, UK : Northampton, MA, USA : Edward Elgar, 2000)
This is a fresh presentation of an interdisciplinary perspective on the possibility of creating a sustainable path of economic development that would not harm the natural environment. Concepts, theories, methods and policy advice are offered on establishing a general notion of sustainability.
Includes bibliographical references and index.
rpm 21/09/2016, ijb 09/04/2019
Loans
Keywords: Sustainable development; Environmental economics -- Brazil; Brazil -- Economic policy; Brazil